Isolation and characterization of endophytic fungi isolated from Ophiorrhiza baviensis as a source of potential anticancer and antioxidant compounds - Nguyen, Mau Hung; Quach, Ngoc Tung; Ho, Ngoc Anh; Doan, Thi Nhung; Hoang, Ha; Chu, Hoang Ha (Vietnam Journal of Biotechnology, 2025)
Endophytic fungi present in internal tissues of medicinal plants are a potent source of natural products with pharmacological and medical activities. Hence, the present study aimed to isolate endophytic fungi from Ophiorrhiza baviensis Drake and assess their anticancer and antioxidant properties. Twelve fungal endophytes were recovered from O. baviensis growing in Cuc Phuong National Park, in which fungi associated with leaves occupied predominantly. Using morphological and 16S rRNA sequence analyses, fungal strains belonged to Ascomycota, with three different genera Colletotrichum (8 strains), Penicillium (2 strains), and Diaporthe (2 strains). The anticancer assays of cancer cell A549 were carried out for the dichloromethane-methanol extracts of these strains. The crude extract of Colletotrichum kahawae XCB2.L7 showed the highest anticancer activities against A549 at the concentration of 20 μg/mL. The TLC analysis revealed that the anticancer drug camptothecin was likely accumulated in mycelia. Further evaluation of anticancer activities revealed the IC50 values of DPPH, hydroxyl radicals, and superoxide radicals were determined to be 431.5 ± 12.4 µg/mL, 534.24 ± 8.4 µg/mL, and 487.0 ± 9.2 µg/mL, respectively. In line with antioxidant activity, C. kahawae XCB2.L7 produced high levels of polyphenol (89.1 ± 5.4 μg GAE/g FW) and flavonoid (114.2 ± 8.6 μg GAE/g FW) contents. These findings shed new light on endophytic fungi from O. baviensis and provided a promising source for exploration of new and commercial compounds.